'It's not good to eat a candy in a wrapper': male students' perspectives on condom use and concurrent sexual partnerships in the eastern Democratic Republic of Congo. Issue 1 (1st January 2018) - Mulumeoderhwa, Maroyi
ABSTRACT: This paper reports on fieldwork carried out in 2011 with aim to investigate young men's perspectives about condoms use, concurrent sexual partnerships and sex in the context of HIV/AIDS. This study employed a qualitative approach to collect data from 28 boys aged 16–20 from two urban and two rural high schools in South Kivu province. Four focus group discussions and 20 individual interviews were conducted among them. The findings showed that most students identified condoms as unsafe and untrustworthy. Reasons given for the mistrust of condoms were related to the belief that condoms do not give enough protection from Sexually Transmitted Infections, HIV and pregnancies. Most participants believe that condoms have a 'small hole' or are unreliable and are therefore not effective in prevention. They also mentioned that condoms encourage inappropriate sexual activity. They prefer flesh-to-flesh sex rather than protected sex using a condom. However, a few participants acknowledged the importance of condom use. Despite the risk of HIV transmission, boys believe that it is appropriate for them to have concurrent sexual partnerships. They justified the concurrent sexual partnerships as a way of ensuring that they cannot miss a girl to satisfy their sexual desire. Given the boys' failure to use condoms and their strong inclination to concurrent sexual partnerships, there is a need for heath groups and stakeholders within the area to increase awareness about condoms' effectiveness and improve knowledge dissemination on Sexually Transmitted Diseases and how they are prevented.